Differentiated Impact of the Common Monetary Policy on the Member States of a Monetary Union : Case of CEMAC - Ngakosso, Antoine (DEMO, 2020)
This paper analyses the misalignments that could result from the common CEMAC monetary policy under macroeconomic stabilization in case of the implementation of the standard Taylor rule by the Central Bank of Central African States (BEAC). Considering a Taylor rule per country solely based on national economic conditions, on the one hand, and another with aggregate data for all countries on the other hand, it transpired that the BEAC ' s monetary policy decision depends on the overall size of the union, whose priority goal is to maintain the fixed parity of its currency with the euro. Thus, its monetary policy has limited efficiency in macroeconomic stabilization due to the asymmetric effects of the common monetary policy. In fact, the BEAC should strengthen its common monetary policy by coordinating national budgetary policies, carry out structural reforms, set up a federal budget and a banking union, obey the Mundell incompatibility triangle or choose a flexible exchange rate regime.(original abstract)